Islamic Social and Political Movements in East Nusa Tenggara A Phenomenological Historical Study - Darajat, Syarifuddin; Hasyim Trabeni, Wahid; Karno, Kamis; Benihingan, Abd. Fatah (Konsultan Surya Buanan, 2025)
This research examines modern Islamic social and political movements in East Nusa Tenggara through a historical phenomenological approach. The study analyzes the dynamics of Islamic movement development in a predominantly non-Muslim region using qualitative methods including in-depth interviews, participatory observation, and document analysis. Results show Islamic movements in NTT have undergone significant transformation influenced by social, political, and cultural factors, adapting to pluralistic conditions while maintaining Islamic identity. The research identifies distinctive patterns in da'wah strategies, political involvement, and social interactions that differ from Muslim-majority regions in Indonesia. The implications are relevant for developing inclusive religious policies, strengthening interfaith dialogue, and creating social development strategies in multi-religious areas. Islamic movements in NTT demonstrate a unique integration model between Islamic values and local wisdom that exemplifies socio-religious harmony in pluralistic societies.